Trajectories of Posttraumatic Stress Symptoms Among Young Adults Exposed to a Typhoon: A Three-Wave Longitudinal Study - Wei Shi; Brian J. Hall (International Journal of Public Health, 2023)
Objective: We used a latent class growth model to identify distinct PTSS trajectories and correlates of these trajectories among young adults who experienced Typhoon Hato, the strongest storm to strike China in the last 50 years.Methods: A longitudinal survey (three-waves) was conducted to explore the mental health status and its correlates among young adults exposed to the typhoon. Data from 362 participants were analyzed via a latent class growth model and multinomial logistic regression.Results: Three distinct classes of PTSS trajectories were identified, including: “resilience” (86.46%), “recovery” (9.12%), and “deterioration” (4.42%). The higher levels of direct typhoon exposure, media use, and posttraumatic growth significantly predicted the higher likelihood of participants being in the “recovery’’ class. In addition, more social support significantly predicted the higher possibility of being in the “resilience” class. Finally, more severe depressive and anxiety symptoms significantly predicted the higher likelihood of being in the “deterioration” class.Conclusion: Further research should develop interventions to enhance protective factors (e.g., posttraumatic growth, media use), decrease risk factors (e.g., depressive and anxiety symptoms), and thereby prevent PTSS.